Single-Port Laparoscopic Assisted Transcrotal Orchidopexy for Palpable Inguinal Canalicular Cryptorchidism Accompany With Indirect Inguinal Hernia - Ma, Yazhen; Cai, Jianhui; Li, Suolin; Wang, Wenbo; Liu, Lin (Frontiers in Pediatrics, 2018)
Purpose To assess the outcomes of a novel laparoscopic assisted transcrotal orchidopexy (LATO) combined with percutaneous extraperitoneal closure (PEC) for palpable inguinal canalicular cryptorchidism accompany with indirect inguinal hernia, and evaluate its safety and efficiency. Materials and Methods A retrospective cohort study for single-port LATO-PEC and traditional inguinal orchidopexy(TIO) was performed between 2011 and 2014. Totally 53 children with both palpable inguinal canalicular testes and indirect inguinal hernia were included. Median patient age was 15month(range, 6 months to 4 years). Of them, 35 patients underwent LATO-PEC procedure, utilizing an umbilical trocar for laparoscope, transcrotal dissection for orchidopexy , and an inner two-hooked cannula for ligation of the patent processus at the level of the internal ring. Three of them were bilateral, 12 on the left side and 20 on the right. Eighteen patients received TIO, seven of them on the left side and 11 on the right. Patient demographics, surgical technique, complications, and clinical outcomes were reviewed. Follow-up visits were performed to reassess position and size of the testes. Results All 56 undescended testes were delivered into the scrotum successfully. In the LATO-PEC group, nine contralateral herniorrhaphy were accomplished simultaneously. Fifteen contralateral patent processus vaginalis (PPVs) in 32 unilateral undescended testis (UDT) were newly confirmed during the laparoscopy, while 6 of them received percutaneous extra-peritoneal herniorrhaphy for visible inguinal bubble in pneumoperitoneum condition. No additional port placement or conversion to open procedure was needed. Mean operative time for unilateral and bilateral LATO-PEC in this study was (37.81±5.23) min and (53.33±2.98) min, respectively. In TIO group, mean operative time was (41.11±8.67)min. There was no statistical difference in operative time between the two approaches for unilateral UDTs (p= 0.098). Median follow-up interval was 24 months(range, 12-84 months). No operative complications were found in either group to date. Conclusions Singe-port LATO-PEC is a safe, effective and cosmetic choice for inguinal canalicular cryptorchidism accompany with indirect inguinal hernia, minimizing injuries to the vas deferens and testicular vessels. Laparoscopy can provide a diagnostic and therapeutic solution of contralateral PPV.